Optimal urban expressway system in a transportation and land use interaction equilibrium framework. Issue 2 (29th November 2019) - Li, Tongfei; Sun, Huijun; Wu, Jianjun; Gao, Ziyou; Ge, Ying-en; Ding, Rui
ABSTRACT: This paper proposes an optimal urban expressway system model with consideration to the interaction equilibrium between transportation and land use. In the suggested model, three kinds of economic agents were examined. Government departments design an optimal urban expressway system in order to maximize the urban system's total utility under a limited budget. However, households and firms choose their locations according to the attractiveness of each traffic zone related to road network accessibility and housing prices. In addition, this optimization problem is formulated as a bi-level program in which the upper-level subprogram maximize the urban system's total utility from the government departments' point of view, whereas the lower-level subprogram uses the transportation and land use equilibrium model. A Genetic Algorithm (GA) was used to solve this mixed integer non-linear programming problem. Finally, this work used numerical experiments to demonstrate the properties of the problem and the performance of our proposed model.